USING EYE TRACKING TO REFRESH RESEARCH METHODOLOGIES - CRINA MARINĂ; OANA BENGA (Studia Universitatis Babes-Bolyai, 2017)
ABSTRACT. Recent literature points to the emergence of a promising methodology that can be used in a wide range of research domains, eye tracking. This paper summarizes the most frequently used indices used in eye tracking and what they relate to in terms of mental processes. Since there is a scarcity of studies that outline and focus on the advantages and disadvantages of employing eye tracking, this overview comprises the main benefits and costs of implementation of this new methodology. Also, there is a slight focus on a comparison to Dot probe task when discussing the advantages and disadvantages. In addition, the paper mentions several applications which stand to highlight the possibilities in using eye tracking. Lastly, there is a summary regarding procedural aspects concerning the type of stimuli, exposure time and input frequency acquirement.